Answers

2015-06-01T16:46:56+08:00

This Is a Certified Answer

×
Certified answers contain reliable, trustworthy information vouched for by a hand-picked team of experts. Brainly has millions of high quality answers, all of them carefully moderated by our most trusted community members, but certified answers are the finest of the finest.
We perform the quadratic formula on a quadratic equation on y:
y = -59x ± √(59²x² + 240x²) = -59x ± √(3481x²+240x²) = -59x ±  √3721x²
                     -30                               -30                             -30
= -59x ± 61x = -x/15 or 4
         -30
So we have (y+x/15)(y-4x)
So we multiply the other by 15 and the other by -1 since we have -15y
²
4x²+59xy-15y² = (15y+x)(4x-y)
0